International Capital Movements under Uncertainty - Grossman, Gene M.; Razin, Assaf (Journal of Political Economy, 1984)
In this paper we analyze the determinants of international movements of physical capital in a model with uncertainty and international trade in goods and securities. In our model, the world allocation of capital is governed, to some extent, by the asset preferences of risk-averse consumer-investors. In a one-good variant in the spirit of the MacDougall model, we find that relative factor abundance, relative labor force size, and relative production riskiness have separate but interrelated influences on the direction of equilibrium capital movements. These same factors remain important in a two-good version with Heckscher-Ohlin production structure. In this case, the direction of physical capital flow is determinate (unlike in a world of certainty) and may hinge on the identity of the factor that is used intensively in the industry with random technology.